Screening of Different Varieties of Brinjal against Insect Pests and their Natural Enemies (Journal of Agriculture and Biology, 2025)
The experiment on screening the brinjal varieties against pests and their natural enemies was carried out at the Latif Farm of SAU, Tandojam. Nine varieties viz. Long-12, Zar-1, Sarwan, Hybrid eggplant, long botanist, round Pakistan, Dil nashhen, Purple king and Tarnab of brinjal varieties were grown on one acre of land. The results revealed that whitefly, jassid, mites, maxican bean beetle and fruit borer appeared on all the varieties of brinjal. The predators like spiders and Brumus sutralis were recorded on all varieties. The results further showed that less whitefly mean population of (7.70± 0.80) per plant was found on Long-12 comparatively resistant, whereas Zar-1 received maximum whitefly population (10.19 ± 0.92) and was found susceptible among all varieties. The comparatively minimum mean population was observed in Long-12 (5.58± 0.77) per plant. Comparatively proved resistant, whereas Dil nasheen received the maximum population of jassid (8.32 ± 0.83) and was found susceptible among all varieties. Minimum Mites mean population was recorded in Tarnab (2.34±0.32) per plant comparatively resistant whereas the maximum mean number was recorded on Sarwan (3.77±0.39) per plant and was found susceptible among all varieties. The minimum mean population of Maxican Bean béetie was recorded in Logn botnist (0.37 ± 0.06) per plant, and the maximum population was found on Zar-1(1.21 ± 0.21) per plant as such Zar-1 was found susceptible among all varieties. The less population of fruit borers was recorded in long -12 (19.39 ± 1.56 5) per plant, and the maximum mean population was recorded on Dil nasheen variety (32.07 ± 2.02%), and Dil nasheen was comparatively susceptible against borer among all varieties. The Pardosa sp. and Agriolis sp. Spider (natural enemies) was found on Round Pakistani (1.36 ± 0.31) per plant. And maximum population on Zar-1 with mean of with mean of (1.80 ± 0.28) per plant and the minimum population Brumus suturalis was recorded on Hybrid eggplant (0.36± 0.24) per plant and the Maximum overall mean number of (0.63 ± 0.23) per plant was recorded on Zar-1 variety.